Strengthening Vocational Learning through Teaching Factory Implementation in Visual Communication Design - Khair, Indratni; Astuti, Sri (Edukasi, 2025)
This study aimed to describe the implementation of the Teaching Factory (TEFA) learning model in Vocational High Schools (SMK), especially in the Visual Communication Design Study Program, using descriptive qualitative methods and purposive sampling techniques. Data were collected through observation, interviews, and documentation. Teaching Factory (TEFA) learning model is designed to integrate teaching and learning activities with real production processes in order to provide practical work experience to students through a production-based approach. The results of the study indicated that TEFA learning at SMK Al-Falah consists of seven systematic steps, namely: implementing design briefs, receiving orders, analyzing orders, stating order readiness, working on orders, conducting quality control, and submitting orders. One prominent characteristic is the "implementing the design brief" stage as a form of adjustment to the needs of the printing industry. This finding showed that the TEFA model not only bridged theoretical and practical learning but also provided a contextual, applicable learning experience that aligns with industry demands. Emphasizing TEFA learning not only represented the real production process but also bridged the gap between school learning and the world of work. Furthermore, it provided real-world work experience and improved students' overall competency, both in terms of technical skills (hard skills) and socio-professional skills (soft skills).